Rinotraqueitis infecciosa bovina (RIB). Caracterización molecular de una cepa colombiana de herpesvirus bovino tipo 1 (2002)
ABSTRACT: Bovine Herpesvirus 1 (BHV-1) affects cattle and is associated with respiratory disease (IBR), reproductive tract disorders (IPV and IPB) and other symptoms which may cause significant economic losses. Serologic studies of prevalence in Colombia indicate that this agent is distributed in relatively wide manner, but the clinic and virological evidence is scarce. It have been proposed therefore that the of HVB-1 strains that exist in this country are different from those circulating in other regions of the world where the virus is tightly associated with disease and economic losses. Several groups have tried to isolate the virus since 1993 ; particularly in our laboratory we have tested 2416 samples, but all these efforts have been unsuccessful. This report is about molecular characterization of only one isolate in the last 20 years, which was obtain by means of corticosteroid treatment of a seropositive bull. The polipeptide and RFLPs profiles indicated that this isolate corresponds to BHV-1 subtype 2b ; which is associated with reproductive symptoms but not with abortion. Altogether, this result is in agreement with the hypotesis that the BHV-1 does not circulate widely in Colombia and are only mildly associated with disease ; therefore, at this point in time this does not seem to be a problem of economic importance in our country.